2022
DOI: 10.3390/math10132171
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Recursive Drug Delivery with Diffusion, Equilibrium, and Convection Coupling

Abstract: In this work, a mathematical model to describe drug delivery from polymer coatings on implants is proposed. Release predictability is useful for development and understanding of drug release mechanisms from controlled delivery systems. The proposed model considers a unidirectional recursive diffusion process which follows Fick’s second law while considering the convective phenomena from the polymer matrix to the liquid where the drug is delivered and the polymer–liquid drug distribution equilibrium. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…The model used in the present study is based on the work of R. Hernandez-Montelongo et al (2022) [ 27 ] and describes the drug delivery process as a unidirectional diffusion, governed by Fick’s second law. The model accounts for convective phenomena from the polymer matrix to the liquid where the drug is delivered, as well as the polymer–liquid drug distribution equilibrium.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model used in the present study is based on the work of R. Hernandez-Montelongo et al (2022) [ 27 ] and describes the drug delivery process as a unidirectional diffusion, governed by Fick’s second law. The model accounts for convective phenomena from the polymer matrix to the liquid where the drug is delivered, as well as the polymer–liquid drug distribution equilibrium.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The model has been solved analytically via a Laplace transformation method [ 27 ]. Conversely, in this study, we use numerical methods to solve this model and compare results to the experimental data.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The proposed model also contemplates a unidirectional recursive diffusion process which follows Fick’s second law while considering the convective phenomena from the polymer matrix to the PBS, where the drug is delivered, and the equilibrium of the polymer–liquid drug distribution. Results indicated that diffusion controls the delivery rate; however, as RB concentration increases, the equilibrium plays an increasing role, becoming the controlling mechanism for a longer time [ 14 ]. These sophisticated mathematical models also allow for determining the drug-concentration profile in the polymer matrix ( Figure 8 ).…”
Section: Mechanisms Of Release Of Cd/ctr-based Biopolymersmentioning
confidence: 99%
“…( B ) Prediction of the drug concentration profile in the HP- -CD/CTR matrix. Adapted from [ 14 ], with permission from MDPI.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation